Economic Feasibility of Rice Straw based Power Generation in Malaysia - M. Shafie, S; Othman, Z; Hami, N (International Journal of Engineering and Technology, 2018)
Malaysia provides a potential in utilising rice straw for electricity generation. However, its implementation is still far away due to the information leak on the financial aspect for local conditions. This paper evaluates the economic feasibility of rice straw life cycle in electricity generation, starting with rice straw collection to electricity generation in Malaysia. For an assumption of 20 years, the cost of electricity generated (COE) is between RM0.72/kWh and RM0.53/kWh for 20 MW to 500 MW respectively. A sensitivity analysis on financial feasibility shows that the most influential parameter to NPV is the sales price. The result from the study will help policy makers obtain the right information regarding the economic potential of rice straw as a fuel in electricity generation in Malaysia.Â Â